Peran Pemerintah Menaikan Kualitas Hidup Masyarakat Lewat Program BSPS - Alfiansyah, Arif; Setiawati, Ririt Iriani Sri; Wahed, Mohammad (Peneliti.net, 2023)
To improve the quality of life of the community, of course, it can be through various aspects. One aspect that can improve the quality of life of the community is to have decent housing. The government's role in efforts to improve the quality of decent housing to help the community, especially low-income people, is the Self-Help Stimulant Assistance Program (BSPS). In this BSPS Program, the author as a companion to the empowerment facilitator is tasked with assisting the implementation of the BSPS program in the Jeruk sub-district of Surabaya City. Which includes the stages of Field Verification, Socialization and Counseling, Self-Help Identification, Group Workshop, Determination of Work Schedules and Material Requests, Construction Assistance. The purpose of this service is to ignore the quality of a livable house and provide knowledge of the importance of decent housing through the role of the community in issuing its self-reliance. The service carried out in the Orange Village of Surabaya through the BSPS program has borne fruit, with the proof that the community is open to the existence of this BSPS program and people who want to spend their self-help in the form of cash, and the existence of mutual assistance between communities to provide assistance in the form of energy in the process of working on the BSPS program house.